Use of Innovative (Micro)Extraction Techniques to Characterise Harpagophytum procumbens Root and its Commercial Food Supplements. Issue 3 (16th November 2017) - Diuzheva, Alina; Carradori, Simone; Andruch, Vasil; Locatelli, Marcello; De Luca, Elisa; Tiecco, Matteo; Germani, Raimondo; Menghini, Luigi; Nocentini, Alessio; Gratteri, Paola; Campestre, Cristina
Abstract: Introduction: For the determination of harpagoside and the wide phenolic pattern in Harpagophytum procumbens root and its commercial food supplements, dispersive liquid–liquid microextraction (DLLME), ultrasound‐assisted DLLME (UA‐DLLME), and sugaring‐out liquid–liquid extraction (SULLE) were tested and compared. Objectives: In order to optimise the extraction efficiency, DLLME and UA‐DLLME were performed in different solvents (water and aqueous solutions of glucose, β‐cyclodextrin, (2‐hydroxypropyl)‐β‐cyclodextrin, sodium chloride, natural deep eutectic solvent, and ionic liquid). Material and Methods: The plant material was ground and sieved to obtain a uniform granulometry before extraction. Commercial food supplements, containing H. procumbens are commercially available in Italy. Results: The most effective sodium chloride‐aided‐DLLME was then optimised and applied for analyses followed by HPLC‐PDA. For comparison, microwave‐assisted extraction was performed using the same solvents and the best results were obtained using 1% of β‐cyclodextrin or 15% of sodium chloride. Conclusion: All commercial samples respected the European Pharmacopoeia monograph for this plant material, showing a harpagoside content ≥ 1.2%. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : Determination of harpagoside and a wide phenolic pattern in H. procumbens root and commercial food supplements, dispersive liquid–liquid microextraction (DLLME), ultrasound‐assisted DLLME, sugaring‐out liquid–liquid extraction, and MAE were tested and compared following HPLC‐PDA analysis.